2010
DOI: 10.1182/blood-2010-03-274811
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of progression of Philadelphia-negative myeloproliferative neoplasms to myelodysplastic syndrome or acute myeloid leukemia by azacitidine: a report on 54 cases on the behalf of the Groupe Francophone des Myelodysplasies (GFM)

Abstract: Transformation of Philadelphia (Ph)-negative myeloproliferative neoplasms (MPNs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(89 citation statements)
references
References 34 publications
3
82
0
4
Order By: Relevance
“…40 Thepot et al evaluated the use of azacitidine in 54 patients with AML or myelodysplastic syndrome secondary to MPN, finding an overall response rate and complete remission rate of 52% and 24%, respectively, with a median overall survival of 11 months. 41 However, in AML patients, the complete remission rate (including complete remission with incomplete count recovery) was only 11%. As in our study, the duration of response was short (9 months); nonetheless azacitidine still represents another promising treatment strategy for patients in this high-risk group, either as a bridge to an allogeneic SCT or for symptomatic improvement.…”
Section: Discussionmentioning
confidence: 99%
“…40 Thepot et al evaluated the use of azacitidine in 54 patients with AML or myelodysplastic syndrome secondary to MPN, finding an overall response rate and complete remission rate of 52% and 24%, respectively, with a median overall survival of 11 months. 41 However, in AML patients, the complete remission rate (including complete remission with incomplete count recovery) was only 11%. As in our study, the duration of response was short (9 months); nonetheless azacitidine still represents another promising treatment strategy for patients in this high-risk group, either as a bridge to an allogeneic SCT or for symptomatic improvement.…”
Section: Discussionmentioning
confidence: 99%
“…[85][86][87][88] Current efforts are investigating diverse agents, including hypomethylating agents, JAK and MEK inhibitors, BCL-X L and BCL-2 inhibitors and clofarabine. [89][90][91][92][93][94] IMPACT OF THE TRANSPLANT-PROCEDURE-AND DONOR-RELATED FACTORS Several prospective multicenter studies have now confirmed the usefulness of RIC-SCT using related or unrelated donors for younger and older patients with MF. In a large retrospective European Group for Blood and Marrow Transplantation study, outcomes from 250 consecutive patients (median age 56 years) with PPV-MF (n = 120) or PET-MF (n = 130) who received allo-SCT, either in MF 'chronic' phase (n = 193) or MF transformed to AML (n = 57), were analyzed.…”
Section: Impact Of Targeting the Jak/signal Transducers And Activatormentioning
confidence: 97%
“…There is no convincing evidence that medical therapies prolong survival in PMF-BP. However, following the encouraging results of azacitidine in high risk MDS, a recent study evaluated its efficacy in transformed MPN (Thepot et al, 2010). An overall response rate of 38% was reported, including 4/7 cases of transformed PMF with a resultant median survival of 8 months.…”
Section: Blast Phase Of Myelofibrosismentioning
confidence: 99%